Determinants of technological innovation in SMEs. Firm-level factors, agglomeration economies and the role of KIBS providers - Roberto Ganau; Eleonora Di Maria (European Regional Science Association (ERSA), 2014)
The study of the determinants of innovation processes has received great attention in both the economics and the business literature. However, only few contributions have proposed a comprehensive framework able to bring together different but not mutually exclusive research approaches. This paper contributes to the analysis of the determinants of technological innovation - namely, product and process innovations - focusing on Italian manufacturing small and medium sized firms (SMEs) by accounting, simultaneously, for firm-specific characteristics, agglomeration economies and the role of KIBS providers. Specifically, the paper provides an empirical investigation which is built on a multi-dimensional theoretical basis which gathers the resource-based view of the firm and the new economic geography framework together. The empirical exercise employs data of about 4,000 Italian SMEs observed over the period 2004-2006 and drawn from the Unicredit-Capitalia database. Parametric probabilistic models are estimated in order to identify the joint effects of several potential determinants of successful technological innovation. Overall, results suggest that technological innovation in manufacturing SMEs is mainly driven by firm-specific characteristics. It emerges that experience and knowledge accumulated over time (i.e. age) as well as availability of human and capital resources (i.e. size) matter for being innovative firms. Moreover, innovative firms show both higher labour productivity levels and higher investments in R&D activities than non-innovative firms. Results partially support previous findings on the agglomeration-innovation relationship: overall, diversification (specialisation) externalities seem to positively (negatively) affect (high-tech) firms' probability of introducing technological innovations. Finally, results suggest that the spatial agglomeration of KIBS providers - i.e. being located in an area characterised by a high concentration of KIBS firms - does not matter per se: in fact, a positive effect emerges only when firms' heterogeneity in absorptive capacity is explicitly considered. Results show that only (low-tech) SMEs which invest in R&D activities benefit from a high geographic concentration of (professional and technological) KIBS firms.
Keywords: D22; O31; R12; 330; Technological innovation; Manufacturing SMEs; Resource-Based Theory; Agglomeration Economies; KIBS providers; Italy